Ercole Pio e le indulgenze di Eger - Domokos, György; Erős, Katalin Renáta (Verbum – Analecta Neolatina, 2015)
The study deals with Ercole Pio, who was the governor of the archbishopric of Eger (Hungary), on behalf of Cardinal Ippolito d’Este between 1508 and 1510. In his letters (kept in the Modena State Archives, but sent from Eger to Ferrara and Rome) written in Italian to his patron, Pio suggested asking Pope Julius II for his permission to sell indulgences in Hungary, in order to increase the income of the archbishopric. The overview of the practice of indulgences in medieval Hungary and the quotations analyzed in the article can illuminate the history of the construction of the Eger cathedral and explain the organisation of economic life in Hungary. Two decades before the battle of Mohács very significant amounts of money had been sent abroad. In several letters Ercole Pio points out that offering 50 percent of the income from the indulgences sold in Eger to the Holy See could perhaps facilitate the permission to be obtained from the Pope.